2003
DOI: 10.1073/pnas.0530206100
|View full text |Cite
|
Sign up to set email alerts
|

ARC5, a cytosolic dynamin-like protein from plants, is part of the chloroplast division machinery

Abstract: Chloroplast division in plant cells is orchestrated by a complex macromolecular machine with components positioned on both the inner and outer envelope surfaces. The only plastid division proteins identified to date are of endosymbiotic origin and are localized inside the organelle. Employing positional cloning methods in Arabidopsis in conjunction with a novel strategy for pinpointing the mutant locus, we have identified a gene encoding a new chloroplast division protein, ARC5. Mutants of ARC5 exhibit defects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
254
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 253 publications
(267 citation statements)
references
References 59 publications
9
254
0
1
Order By: Relevance
“…The protein machine of chloroplasts, unlike that of bacteria, can be observed in electron micrographs of thin sections. One possible reason for its visibility is that this machine consists of at least three layers: an innermost ring comprising FtsZ, followed by the plastid dividing ring that is visible by negative staining but is of unknown composition 102 , and an outermost ring on the outside of the organelle that contains a dynamin-like protein (DRP) 103,104 . Dynamins are eukaryotic GTPases that assemble on membranes and mediate membrane fission 97 ; dynamin also has a role in cytokinesis of animal and plant cells 105,106 .…”
Section: Ftsz and Organelle Division Plastid Divisionmentioning
confidence: 99%
“…The protein machine of chloroplasts, unlike that of bacteria, can be observed in electron micrographs of thin sections. One possible reason for its visibility is that this machine consists of at least three layers: an innermost ring comprising FtsZ, followed by the plastid dividing ring that is visible by negative staining but is of unknown composition 102 , and an outermost ring on the outside of the organelle that contains a dynamin-like protein (DRP) 103,104 . Dynamins are eukaryotic GTPases that assemble on membranes and mediate membrane fission 97 ; dynamin also has a role in cytokinesis of animal and plant cells 105,106 .…”
Section: Ftsz and Organelle Division Plastid Divisionmentioning
confidence: 99%
“…In mammalian cells, fission of the mitochondrion (reviewed in Westermann, 2008) does not involve Ftsz. Dynamin-like proteins are known to be involved in mitochondrial fission in some organisms, including yeast and Caenorhabditis elegans (Bleazard et al, 1999;Labrousse et al, 1999), and also in the fission of plastids in plants (Gao et al, 2003;Miyagishima et al, 2003). It is known that Plasmodium and other apicomplexa encode dynamin proteins, one of which (dynamin-2) is similar to dynamin-like proteins that are known to be involved in mitochondrial fission in other organisms (Vaishnava and Striepen, 2006).…”
Section: Examination Of the Apicoplast Throughout The P Berghei Lifementioning
confidence: 99%
“…Here, Ftsz proteins form a ring structure within the stroma of the chloroplast, seemingly constricting the organelle in a drawstring action (reviewed in Margolin, 2005). Other proteins, including dynamin, are then recruited to the constricted regions of the chloroplast and this leads to fission of the organelle (Gao et al, 2003;Miyagishima et al, 2003). In the case of the mitochondrion, proteins, including dynamin, are similarly recruited to sites of constriction and appear to lead to mitochondrial fission (Bleazard et al, 1999;Labrousse et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Although many nuclear genes that contribute functional components to the organelle have been described, including those of endosymbiotic origin that control division from within the organelle (Osteryoung et al, 1998), very few regulatory genes have been identified even in model organisms. One example, Accumulation and Replication of Chloroplasts5, encodes a cytoplasmically localized dynamin-like protein that regulates chloroplast division in Arabidopsis thaliana (Gao et al, 2003). A second example, the Golden2-like (GLK) genes, encode transcription factors that regulate chloroplast development in diverse species, namely in the monocot maize (Zea mays) and in the eudicot Arabidopsis (Langdale and Kidner, 1994;Hall et al, 1998;Rossini et al, 2001;Fitter et al, 2002).…”
Section: Introductionmentioning
confidence: 99%